2011
DOI: 10.1021/ol201665c
|View full text |Cite
|
Sign up to set email alerts
|

Iodonium Salts Are Key Intermediates in Pd-Catalyzed Acetoxylation of Pyrroles

Abstract: A mild, room-temperature Pd-catalyzed acetoxylation of pyrroles with phenyliodonium acetate is described. The acetoxylation was found to proceed via the initial formation of pyrrolyl(phenyl)iodonium acetates, which were converted to acetoxypyrroles in the presence of Pd(OAc)(2). The acetoxylation could also be carried out as a one-pot sequential procedure without the isolation of the intermediate iodonium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…The absence of 1,2‐migration confirmed the importance of choosing an appropriate oxidant, capable of fast oxidation of the C3–Pd II bond in 178 , leading to easy reductive elimination and C–O bond formation from 179 . In 2011, Suna isolated indolyl(phenyl)iodonium acetate salts 180 as alternative intermediates, mainly for electron‐rich heterocycles such as indoles and pyrroles . Then, through the action of Pd, the transfer of the electron‐rich moiety rather than the sterically less hindered aryl group generated the desired products by a one‐pot sequential protocol.…”
Section: Intermolecular Acyloxylationmentioning
confidence: 99%
“…The absence of 1,2‐migration confirmed the importance of choosing an appropriate oxidant, capable of fast oxidation of the C3–Pd II bond in 178 , leading to easy reductive elimination and C–O bond formation from 179 . In 2011, Suna isolated indolyl(phenyl)iodonium acetate salts 180 as alternative intermediates, mainly for electron‐rich heterocycles such as indoles and pyrroles . Then, through the action of Pd, the transfer of the electron‐rich moiety rather than the sterically less hindered aryl group generated the desired products by a one‐pot sequential protocol.…”
Section: Intermolecular Acyloxylationmentioning
confidence: 99%
“…Recent results from our group, however, call to question the involvement of electrophilic palladation in the acetoxylation of electron-rich heterocycles [9]. Thus, we have demonstrated that the Pd-catalyzed acetoxylation of pyrroles and indoles with PhI(OAc) 2 in AcOH proceeds via the initial formation of pyrrolyl(phenyl)iodonium acetates 4, which have been isolated and characterized.…”
Section: Methodsmentioning
confidence: 77%
“…The heteroaryliodonium salts 4 were stable in AcOH solutions; however, in the presence of Pd(OAc) 2 they were smoothly transformed into C-2 or C-3 acetoxypyrroles* and C-3 acetoxyindoles. Notably, non-catalyzed thermal decomposition of pyrrolyl(phenyl)iodonium acetates 4 afforded a complex mixture of acetoxylated pyrrole 5, iodopyrrole, and the starting pyrrole 3 [9]. The acetoxylation could also be carried out as a one-pot sequential procedure without the isolation of the intermediate iodonium salts 4 (Scheme 4).…”
Section: Methodsmentioning
confidence: 99%
“…With the optimal reaction conditions to hand, the substrate scope of the indole substrate was extended to N-benzylindole (entries [1][2][3][4][5], N-methylindole (entry 6), N-isobutenylindole (entries [7][8][9][10][11][12], N-n-butylindole (entries [13][14][15][16][17][18], and the results * Correspondent. E-mail: kamenzxh@163.com are summarised in Table 2.…”
Section: Resultsmentioning
confidence: 99%